2017
DOI: 10.1371/journal.pone.0184366
|View full text |Cite
|
Sign up to set email alerts
|

Large scale expression and purification of secreted mouse hephaestin

Abstract: Hephaestin is a large membrane-anchored multicopper ferroxidase involved in mammalian iron metabolism. Newly absorbed dietary iron is exported across the enterocyte basolateral membrane by the ferrous iron transporter ferroportin, but hephaestin increases the efficiency of this process by oxidizing the transported iron to its ferric form and promoting its release from ferroportin. Deletion or mutation of the hephaestin gene leads to systemic anemia with iron accumulation in the intestinal epithelium. The cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…We confirmed that immunoreactivity for hephaestin was observed in the cytoplasm of human brain astrocytes. Hephaestin, also known as a ferroxidase, was reported to be expressed in a secreted form . Burkhart et al reported that immunoreactivity for hephaestin was localized at both the cellular membrane and cytoplasm using primary astrocytes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed that immunoreactivity for hephaestin was observed in the cytoplasm of human brain astrocytes. Hephaestin, also known as a ferroxidase, was reported to be expressed in a secreted form . Burkhart et al reported that immunoreactivity for hephaestin was localized at both the cellular membrane and cytoplasm using primary astrocytes .…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the ferroportin‐hepcidin system likely represents the main pathway for cellular iron egress and also regulates cellular iron levels in astrocytes. Hephaestin is known to be a large membrane‐anchored multicopper ferroxidase involved in iron metabolism . Dietary iron is exported across the basolateral membrane of enterocytes by the ferrous iron transporter ferroportin, and hephaestin increases the efficiency of this process by oxidizing the transported iron to its ferric form and promoting its release from ferroportin.…”
Section: Introductionmentioning
confidence: 99%
“…RBD Wuhan was produced in a system of baculovirus/insect cells and purified as reported (we thank these authors for providing the plasmid). The protein (residues Arg319-Phe541 of S Wuhan ) hosts a C-terminal 6×His-tag and is exported to the culture medium thanks to a gp67 signal peptide that is cleaved upon exportation …”
Section: Methodsmentioning
confidence: 99%
“…Hp has 50% sequence similarity with Cp, including the conservation of multiple copper binding sites (Vulpe et al, 1999;Griffiths et al, 2005) and is highly expressed in sla mouse intestine. Interestingly, in sla mice, this gene shows an in-frame deletion of 194 amino acids, probably resulting in a non-functional product (Ranganathan et al, 2012a;Deshpande et al, 2017). The researchers conclude that this protein is a transmembrane-bound ferroxidase that plays an important role in the iron export mechanism involving FPN and Tf (Hudson et al, 2008;Vashchenko and Macgillivray, 2012;Lee et al, 2012;Zheng et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…
Once inside the enterocyte, the iron can be stored or exported across the enterocyte basolateral membrane by the ferrous iron exporter ferroportin (FPN) (Knutson, 2017). Hephaestin (Hp) increases the efficiency of this process by oxidising the transported iron to its ferric form and promoting its release from FPN (Crichton, 2009;Han, 2011;Lawen and Lane, 2013;Deshpande et al, 2017), from which it is rapidly bound to apo-Tf for transport in the circulation to tissues (Lawen and Lane, 2103;Knutson, 2017). In short, Hp plays a role in the uptake of iron from the diet, whereas Cp helps with the redistribution of iron to the cells and tissues; however, how Hp interacts with Tf, Cp, and FPN is still unclear.To understand this mechanism, iron metabolismdisordered animals, e.g., knockout (KO) mice and sla mice, have been studied as useful models of iron homeostasis.
…”
mentioning
confidence: 99%